2020
DOI: 10.21203/rs.3.rs-30058/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of workload, mental health and professional quality of life on healthcare workers’ hand hygiene behavior in medical aid during COVID-19 pandemic

Abstract: BackgroundAppropriate hand hygiene behavior is much crucial during COVID-19 pandemic, which is influenced by workload, mental health and professional quality of life. The increasing workload, worse mental health and negative professional quality of life are severe challenges for healthcare workers, whereas the evidence of mechanism between them and hand hygiene behavior are limited. This study aimed to understand and model how HCWs’ hand hygiene behaviors were influenced by workload, mental health and professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…In our study, those who needed information on “infection prevention control” and “use of PPE” to improve their skills had lower quality of life and higher hopelessness in various health-related areas, and that those who needed information on “case management” had higher state anxiety. This result confirms the hypothesis (H4) that “Knowledge-skills about COVID-19 affect anxiety and hopelessness levels, and quality of life in the areas of physical, mental, social, and environmental health” and is similar to research findings showing the relationship between life expectancy and quality of life (Pappa et al, 2020; Zhou & Zhang, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, those who needed information on “infection prevention control” and “use of PPE” to improve their skills had lower quality of life and higher hopelessness in various health-related areas, and that those who needed information on “case management” had higher state anxiety. This result confirms the hypothesis (H4) that “Knowledge-skills about COVID-19 affect anxiety and hopelessness levels, and quality of life in the areas of physical, mental, social, and environmental health” and is similar to research findings showing the relationship between life expectancy and quality of life (Pappa et al, 2020; Zhou & Zhang, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Besides, those who needed information on "case management" had higher state anxiety levels, which is parallel with the literature. 3,38,49 During the Covid-19 pandemic, hope is one of the main coping strategies and a resource that affects HCWs' ability to interact in stressful life-threatening situations. 50 Therefore, in this period, to raise the hope of HCWs and strengthen effective coping mechanisms, supporting the initiatives to prevent infection (education, hand hygiene, equipment support, etc.)…”
Section: Hcwsmentioning
confidence: 99%
“…COVID-19 pandemic is a global threat that is currently being an attention in every country. The government's strict movement restrictions to reduce the spread of COVID-19 are likely having a negative impact on people's mental health [13], [27]. By this research, a pandemic situation as now becomes a burden to societ that gives the rise to psychological disorders in terms of both patients and health professionals.…”
Section: Barrierss and Challenges Based On Individualsmentioning
confidence: 84%
“…A former study reported that nurses and physicians in COVID-19 wards experienced moderate job burnout and compassion satisfaction 37 . Another study showed that during the COVID-19 pandemic, healthcare providers had moderate compassion satisfaction, job burnout, and secondary traumatic stress 38 . These ndings are due to the fact that nurses are in the frontline of care delivery to patients with COVID-19 and hence, are at great risk for psychological disorders such as depression, which in turn increases their fatigue and reduces their PQOL 39 .…”
Section: Discussionmentioning
confidence: 99%